Electrolyte additive composition and application thereof
By using an additive composition of boron trifluoride composite metal salt of pyrosulfate and sulfate in the lithium-ion/sodium-ion battery electrolyte, the problem of poor stability of the battery in high temperature and high voltage environments is solved, and a better battery life is achieved. High and low temperature performance.
Patent Information
- Application Number
- CN202310883902.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
The existing lithium-ion/sodium ion battery electrolyte additives have poor stability in high temperature and high voltage environments, affecting the high-temperature storage and cycling performance of the battery.
An additive composition containing boron trifluoride pyrosulfate composite metal salt and sulfate is used to improve the stability of the battery interface film through the combination of cross-linked network structure and SO42- particles.
On the basis of maintaining the advantages of battery impedance and low temperature performance, the high temperature storage and circulation performance of the battery significantly improves the battery, and enhance the stability of the battery at high temperature and high voltage.
Smart Images

Figure CN119340478A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion / sodium ion battery electrolytes, and in particular to an additive composition comprising a pyrosulfate boron trifluoride composite metal salt and a sulfate, and an application of the additive composition in electrolyte preparation, as well as an application of the prepared electrolyte in a lithium ion secondary battery or a sodium ion secondary battery. Background Art
[0002] As an indispensable component of lithium / sodium ion batteries, electrolyte additives are mainly responsible for constructing the electrode / electrolyte interface film to achieve electronic insulation and facilitate lithium ion transmission. Under the influence of different functional groups of additives, the composition and structure of the electrode / electrolyte interface film change, ultimately affecting the battery cycle life, high-temperature storage, and low-temperature discharge performance.
[0003] Pyrosulfate boron trifluoride composite lithium salt is a new electrolyte additive developed by Zhejiang Chemical Research Institute Co., Ltd. Its patent CN202211583064.X discloses that the additive can improve the battery's cycle performance, high-temperature storage performance and low-temperature performance. At the same time, patent CN202211583043.8 also discloses the use of pyrosulfate boron trifluoride composite lithium salt, vinyl sulfate and / or 1,3-propane sultone in combination, or the further addition of vinylene carbonate in combination, so that lithium-ion batteries still have excellent cycle performance, high-temperature storage performance and the effect of inhibiting battery gas production in high energy density systems and high voltage environments, and can inhibit the impedance growth during the battery cycle and further improve low-temperature performance. However, although vinyl sulfate has excellent electrochemical properties, its poor stability is also well known to aggravate the problem of electrolyte discoloration, and 1,3-propane sultone is gradually subject to European REACH regulations due to its carcinogenicity.
[0004] Therefore, it is also an important research topic to continue in-depth research to develop more stable, safe and environmentally friendly pyrosulfate boron trifluoride complex metal salt compositions and electrolyte formulas to meet the battery needs of different scenarios and different performances. Summary of the invention
[0005] In order to solve the above technical problems, the present invention further proposes an additive composition comprising a pyrosulfate boron trifluoride composite metal salt and a sulfate, and its application in electrolyte preparation and in lithium-ion batteries or sodium-ion batteries. The additive composition can further improve the high-temperature storage performance and high-temperature cycle performance of the battery while maintaining the high and low temperature performance of the pyrosulfate boron trifluoride composite metal salt, and will not increase the initial impedance of the battery.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] An electrolyte additive composition, the additive composition comprising:
[0008] The first additive comprises at least a pyrosulfate boron trifluoride composite metal salt having a structure shown in the following formula (I-1):
[0009]
[0010] The second additive is selected from sulfates having structures shown in the following formulas (II) and / or (III):
[0011]
[0012] Wherein, M is Li or Na; and the first additive and the second additive are both Li salt or both Na salt;
[0013] The mass ratio of the second additive to the first additive is (0.001-0.1):1, and the preferred mass ratio is (0.01-0.1):1.
[0014] The first additive further comprises at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6), and the first additive contains at least 80 wt % or more of the pyrosulfate boron trifluoride composite metal salt having the structure represented by the formula (I-1):
[0015]
[0016]
[0017] In formulas (I-2), (I-3), (I-4), (I-5), and (I-6), M is Li or Na.
[0018] The first additive contains at least 80 wt % of the pyrosulfate boron trifluoride composite metal salt having the structure represented by formula (I-1).
[0019] Preferably, the first additive contains 80 to 95 wt % of the pyrosulfate boron trifluoride complex salt having the structure represented by the formula (I-1), and the rest is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).
[0020] The second additive of the present invention specifically comprises sulfates represented by the following structures (II-1), (II-2), (III-1), and (III-2):
[0021]
[0022] The additive composition of the present invention can be prepared by reacting pyrosulfate with boron trifluoride, wherein the pyrosulfate can be prepared by first reacting an inorganic lithium salt with dilute sulfuric acid to obtain hydrogen sulfate, and then thermally decomposed. In the thermal decomposition process of the hydrogen sulfate, in addition to pyrosulfate, a small amount of sulfate is also generated. The additive composition thus prepared is mainly the first additive and contains a small amount of the second additive. By adjusting the thermal decomposition temperature of the hydrogen sulfate or performing post-treatment, the content of the second additive in the additive composition can also be reduced until it is completely removed.
[0023] The first additive of the present invention is mainly composed of compound I-1. By adjusting the preparation process, a mixture containing at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6) and compound I-1 can also be obtained.
[0024] The -BOSOSOB- structure of the first additive of the present invention easily forms a cross-linked network structure. Although it can provide a large number of ion transmission channels, the stability of this cross-linked network structure is poor under high temperature and high voltage. 2- The combination of particles and boron atoms in the network structure can further enhance the stability of the interface film, thereby further improving the performance of the battery at high temperature and high voltage while maintaining the advantages of impedance, room temperature and low temperature performance.
[0025] The present invention also provides a method for preparing an electrolyte, the method comprising: adding a main salt to a non-aqueous solvent until the molar concentration of the main salt is 0.1 to 4.0 mol / L, and then continuing to add any of the above-mentioned additive compositions to obtain an electrolyte, and making the first additive account for 0.1 to 15.0 wt% of the total mass of the electrolyte, and the second additive accounts for 0.001 to 0.5 wt% of the total mass of the electrolyte.
[0026] Preferably, in the electrolyte, the first additive accounts for 0.1-10.0 wt % of the total mass of the electrolyte, and the second additive accounts for 0.01-0.5 wt % of the total mass of the electrolyte.
[0027] Since additives are consumed in constructing interface films at the interfaces of the positive and negative electrodes of the battery during battery formation and capacity separation, there is a certain difference between the additive content detected in actual battery products and the amount added during the electrolyte preparation process. Therefore, the amount of additive added in the preparation method of the present invention is not necessarily equivalent to the content in the electrolyte liquid in the battery.
[0028] The main salt is selected from a main lithium salt or a main sodium salt.
[0029] The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate, and lithium difluorobis(oxalate) phosphate; preferably, the main lithium salt is selected from lithium hexafluorophosphate and / or lithium bis(fluorosulfonyl imide), and the molar concentration in the non-aqueous solvent is 0.5-2.0 mol / L.
[0030] The main sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium difluorophosphate, sodium bisoxalatoborate, sodium difluorooxalatoborate, sodium bistrifluoromethylsulfonyl imide or sodium bisfluorosulfonyl imide; preferably, the main sodium salt is selected from sodium hexafluorophosphate and / or sodium bisfluorosulfonyl imide, and the molar concentration in the non-aqueous solvent is 0.5-2.0 mol / L.
[0031] The non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds;
[0032] Preferably, the C3-C6 carbonate or fluorocarbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate or ethyl propyl carbonate; the C3-C8 carboxylic acid ester or fluorocarboxylic acid ester compound is selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate and propyl propionate; the sulfone compound is selected from at least one of cyclopentane sulfoxide, dimethyl sulfoxide, dimethyl sulfone or diethyl sulfone; the ether compound is selected from triethylene glycol dimethyl ether and / or tetraethylene glycol dimethyl ether.
[0033] Generally, the non-aqueous solvent in the lithium ion battery electrolyte and the sodium ion battery electrolyte can be the same. Therefore, the above non-aqueous solvent can be applied to the lithium ion battery electrolyte or the sodium ion battery electrolyte.
[0034] In a specific embodiment, the non-aqueous solvent is a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), and the mass ratio of the three is EC:EMC:DEC=4:4:2, which has better comprehensive performance.
[0035] In another specific embodiment, the non-aqueous solvent is a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC), and the mass ratio of the four is EC:EMC:DEC:DMC=3:5:1:1, which can further improve the ionic conductivity of the electrolyte on the basis of having better comprehensive performance.
[0036] In another specific embodiment, the non-aqueous solvent is a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and methyl acetate (EA), and the mass ratio of the four is EC:EMC:DEC:EA=2:5:1:2. It has a lower freezing point on the basis of having better comprehensive performance, which can further improve the low-temperature performance of the electrolyte.
[0037] In order to improve the comprehensive performance of the lithium-ion battery, a basic additive can also be added to the lithium-ion battery electrolyte, and the basic additive is selected from at least one of fluoroethylene carbonate, vinylene carbonate, tris(trimethylsilyl)phosphate, 1,3-propane sultone, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorobis(oxalate)phosphate or lithium difluorobis(oxalate)borate, and any one of the basic additives accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte.
[0038] In a specific embodiment, the basic additives are vinylene carbonate and lithium difluorophosphate, each accounting for 0.1% to 2% of the total mass of the electrolyte. By using them in combination with the first additive and the second additive, the room temperature cycle and high temperature cycle performance of the battery can be further improved.
[0039] In another specific embodiment, the basic additive is 1,3-propane sultone and tris(trimethylsilyl) phosphate, each accounting for 0.1% to 2% of the total mass of the electrolyte. By using it in combination with the first additive and the second additive, the gas production of the lithium battery during high-temperature storage can be further suppressed, and the initial impedance of the battery can be reduced, thereby improving the low-temperature performance.
[0040] Generally, the basic additives in lithium ion battery electrolyte and sodium ion battery electrolyte can be the same, the only difference is that the anions in the salt additives contained in the basic additives are different. Therefore, in order to improve the comprehensive performance of sodium ion batteries, basic additives can also be added to the sodium ion battery electrolyte, and the basic additives are selected from at least one of fluoroethylene carbonate, vinylene carbonate, tris(trimethylsilyl)phosphate, 1,3-propane sultone, sodium difluorophosphate, sodium bisfluorosulfonyl imide, succinic anhydride, adiponitrile, cyclohexylbenzene, sodium difluorobisoxalate phosphate or sodium difluorooxalate borate, and any one of the basic additives accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte.
[0041] The present invention also provides a lithium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the lithium ion secondary battery is prepared by the following method:
[0042] The positive electrode sheet, the separator, and the negative electrode sheet are wound together to form a core, sealed with an aluminum-plastic film and then baked. After that, the electrolyte obtained by any of the above-mentioned preparation methods is injected into it, and a lithium-ion secondary battery is obtained after standing, forming, grading, and aging.
[0043] The active material of the positive electrode sheet of the lithium-ion battery is selected from nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium cobaltate materials, or lithium iron phosphate materials, and the active material of the negative electrode sheet is selected from graphite, silicon-carbon, silicon monoxide, silicon, tin, metallic lithium, or their composite materials.
[0044] The present invention also provides a sodium-ion secondary battery, including a positive electrode sheet, a negative electrode sheet, and a separator. The sodium-ion secondary battery is obtained by the following method:
[0045] The positive electrode sheet, the separator, and the negative electrode sheet are wound together to form a core, sealed with an aluminum-plastic film and then baked. After that, the electrolyte obtained by any of the above-mentioned preparation methods is injected into it, and a sodium-ion secondary battery is obtained after standing, forming, grading, and aging.
[0046] The negative electrode of the sodium-ion battery is one or more of hard carbon, carbon black, amorphous carbon, graphite, SnS2, Na2Ti3O7, silicon-based materials, metal oxides, metal sulfides, or metallic sodium; the positive electrode material is NaMn (1-x-y) Ni y M x O2 (0 ≤ x, y ≤ 1, M is Cu, Fe, Co), sodium manganate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron phosphate, sodium manganese phosphate, Na x MnFe(CN)6 (0 < x ≤ 2) or one or more of them.
[0047] Compared with the prior art, the beneficial effects of the present invention include:
[0048] The additive composition of the present invention has a synergistic effect in constructing a stable electrode / electrolyte interface. The pyrosulfate boron trifluoride composite metal salt as the first additive has a -B-O-S-O-S-O-B- structure, which can form a cross-linked network structure to provide a large number of ion transport channels, thereby increasing the ionic conductivity and reducing the interfacial film impedance; at the same time, the O on the S=O bond in the structure of the first additive can also combine with the metal atoms on the surface of the battery positive electrode to improve the protection of the positive electrode. However, the interfacial film with a cross-linked network structure formed by the first additive becomes less stable at high temperatures and high voltages. When used in combination with the sulfate as the second additive, an appropriate amount of SO4 in the second additive 2-The particles can combine with the boron atoms in the cross-linked network structure to improve the stability of the interface film. Therefore, through the combination of the first additive and the second additive, the battery can further improve the high temperature performance of the battery under high temperature and high voltage environment while maintaining the advantages of impedance and low temperature performance, so that the battery has better high and low temperature performance. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0050] In the embodiments and comparative examples of the present invention, the types of the first additive include the following:
[0051] The first additive A contains 95 wt% of compound I-1 and 5 wt% of compound I-2, both of which are composite lithium salts;
[0052] The first additive B contains 90 wt% of compound I-1, 6 wt% of compound I-2 and 4 wt% of compound I-3, and all of them are composite lithium salts;
[0053] The first additive C contains 85 wt % of compound I-1, 7 wt % of compound I-2, 5 wt % of compound I-3 and 3 wt % of compound I-4, and all of them are composite lithium salts.
[0054] The first additive D contains 95 wt % of compound I-1 and 5 wt % of compound I-2, and both are complex sodium salts.
[0055] 1. Preparation of electrolyte
[0056] Preparation of basic electrolyte 1: In a glove box filled with argon (water content <5 ppm, oxygen content <10 ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are evenly mixed in a mass ratio of EC:EMC:DEC=3:5:2, and lithium hexafluorophosphate (LiPF6) is slowly added to the mixed solution until the molar concentration of LiPF6 is 1.2 mol / L to obtain basic electrolyte 1.
[0057] Preparation of basic electrolyte 2: In a glove box filled with argon (water content <5 ppm, oxygen content <10 ppm), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are evenly mixed in a mass ratio of EC:EMC:DEC = 4:4:2, and sodium hexafluorophosphate (NaPF6) is slowly added to the mixed solution until the molar concentration of NaPF6 is 1.2 mol / L to obtain basic electrolyte 2.
[0058] Example 1
[0059] 0.5 wt % of the first additive A and 0.01 wt % of the second additive II-1 were added to the basic electrolyte 1 to obtain the electrolyte of this embodiment.
[0060] Example 2
[0061] The operation of this embodiment is the same as that of Embodiment 1, except that the addition amount of the first additive A is adjusted to 1 wt %, and the addition amount of the second additive II-1 is adjusted to 0.001 wt %, to obtain the electrolyte of this embodiment.
[0062] Example 3
[0063] The operation of this embodiment is the same as that of Embodiment 1, except that the addition amount of the first additive A is adjusted to 1 wt %, and the addition amount of the second additive II-1 is adjusted to 0.1 wt %, to obtain the electrolyte of this embodiment.
[0064] Example 4
[0065] The operation of this embodiment is the same as that of Embodiment 1, except that the addition amount of the first additive A is adjusted to 2 wt %, and the addition amount of the second additive II-1 is adjusted to 0.1 wt %, to obtain the electrolyte of this embodiment.
[0066] Example 5
[0067] The operation of this embodiment is the same as that of Embodiment 1, except that the addition amount of the first additive A is adjusted to 2 wt %, and the addition amount of the second additive II-1 is adjusted to 0.3 wt %, to obtain the electrolyte of this embodiment.
[0068] Example 6
[0069] The operation of this embodiment is the same as that of Embodiment 1, except that the addition amount of the first additive A is adjusted to 5 wt %, and the addition amount of the second additive II-1 is adjusted to 0.3 wt %, to obtain the electrolyte of this embodiment.
[0070] Example 7
[0071] The operation of this embodiment is the same as that of Embodiment 1, except that the addition amount of the first additive A is adjusted to 10 wt %, and the addition amount of the second additive II-1 is adjusted to 0.5 wt %, to obtain the electrolyte of this embodiment.
[0072] Example 8
[0073] The operation of this embodiment is the same as that of Embodiment 3, except that the second additive is replaced by Compound III-1 from Compound II-1 to obtain the electrolyte of this embodiment.
[0074] Example 9
[0075] The operation of this embodiment is the same as that of Embodiment 3, except that the first additive A is replaced by the first additive B, and the second additive is replaced by the compound II-1 by the compound III-1, and the other parts remain unchanged to obtain the electrolyte of this embodiment.
[0076] Example 10
[0077] The operation of this embodiment is the same as that of Embodiment 3, except that the first additive A is replaced by the first additive C, and the second additive is replaced by the compound II-1 by the compound III-1, and the other parts remain unchanged to obtain the electrolyte of this embodiment.
[0078] Embodiment 11
[0079] The operation of this embodiment is the same as that of embodiment 3, except that 1% of vinylene carbonate (VC) is added to the electrolyte of embodiment 3 to obtain the electrolyte of this embodiment.
[0080] Example 12
[0081] The operation of this embodiment is the same as that of Embodiment 3, except that 1% of 1,3-propane sultone (PS) is added to the electrolyte of Embodiment 3 to obtain the electrolyte of this embodiment.
[0082] Example 13
[0083] The operation of this embodiment is the same as that of Embodiment 8, except that 1% of vinylene carbonate (VC) and 1% of lithium difluorophosphate (LiDFP) are added to the electrolyte of Embodiment 8 to obtain the electrolyte of this embodiment.
[0084] Embodiment 14
[0085] 1.0 wt % of the first additive D and 0.1 wt % of the second additive II-2 were added to the basic electrolyte 2 to obtain the electrolyte of this embodiment.
[0086] Embodiment 15
[0087] The operation of this embodiment is the same as that of Embodiment 14, except that the second additive is replaced by Compound III-2 from Compound II-2, and the other parts remain unchanged to obtain the electrolyte of this embodiment.
[0088] Example 16
[0089] The operation of this embodiment is the same as that of Embodiment 15, except that 1 wt % of diethyl sulfate (DTD) is added to Embodiment 15 to obtain the electrolyte of this embodiment.
[0090] Comparative Example 1
[0091] The operation of this comparative example is the same as that of Example 2, except that the second additive is not added to obtain the electrolyte of this comparative example.
[0092] Comparative Example 2
[0093] The operation of this comparative example is the same as that of Example 9, except that the second additive is not added to obtain the electrolyte of this comparative example.
[0094] Comparative Example 3
[0095] The operation of this comparative example is the same as that of Example 5, except that the first additive is not added to obtain the electrolyte of this comparative example.
[0096] Comparative Example 4
[0097] The operation of this comparative example is the same as that of Example 9, except that the addition amount of the second additive is adjusted to 1 wt % to obtain the electrolyte of this comparative example.
[0098] Comparative Example 5
[0099] The operation of this comparative example is the same as that of Example 9, except that the addition amount of the second additive is adjusted to 3 wt % to obtain the electrolyte of this comparative example.
[0100] Comparative Example 6
[0101] The electrolyte of this comparative example was obtained by using the basic electrolyte 1.
[0102] Comparative Example 7
[0103] The operation of this comparative example is the same as that of Example 15, except that the second additive is not added to obtain the electrolyte of this comparative example.
[0104] Comparative Example 8
[0105] The operation of this comparative example is the same as that of Example 15, except that the first additive is not added to obtain the electrolyte of this comparative example.
[0106] Comparative Example 9
[0107] The electrolyte of this comparative example was obtained by using the basic electrolyte 2.
[0108] 2. Electrochemical performance test
[0109] The electrolytes of Examples 1 to 13 and Comparative Examples 1 to 6 are respectively made into soft-pack lithium-ion batteries with a capacity of 1260 mAh. The lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material is a ternary positive electrode LiNi 0.6 Co 0.2 Mn 0.2O2, the negative electrode active material is high-capacity graphite. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished lithium-ion battery soft pack cell is obtained through the steps of standing, forming, capacity separation and aging.
[0110] The electrolytes of Examples 14 to 16 and Comparative Examples 7 to 9 were respectively made into sodium ion batteries with a soft pack capacity of 1000 mAh. The sodium ion batteries included a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material was a ternary positive electrode NaNi 0.33 Fe 0.33 Mn 0.33 O2, the negative electrode active material is hard carbon. The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum plastic film and then baked to make the electrode moisture meet the requirements, and the battery cell is injected with electrolyte after baking, and the finished sodium ion soft-pack battery cell is obtained through the steps of standing, forming, volume separation and aging.
[0111] The performance test (2.8-4.4V) of the lithium-ion battery and sodium-ion battery prepared above mainly includes:
[0112] (1) 60°C high temperature storage test: The battery was charged to 100% SOC and stored in a 60±2°C oven for 28 days. The volume before and after storage was tested to obtain the volume expansion rate of the single battery before and after 60°C storage.
[0113] (2) 45°C high temperature cycle test: The battery is cycled in a 45±1°C oven at a charge and discharge current of 1C / 1C. The discharge capacity per week is calculated. The cycle is stopped after 500 cycles, and the capacity retention rate after the cycle is calculated.
[0114] (3) -20℃ low-temperature discharge: The battery is discharged in a -20±1℃ oven at a discharge current of 1C to 80% of the lower limit voltage. The low-temperature discharge capacity is taken as the percentage of the 1C discharge capacity at 25℃, which is recorded as the low-temperature discharge capacity retention rate.
[0115] The test results are shown in Table 1 below:
[0116] Table 1 Battery electrochemical performance test results
[0117]
[0118]
[0119] Examples 1 to 13 and Comparative Examples 1 to 6 in Table 1 are the electrochemical performance test results of the additive composition applied to lithium-ion batteries. By comparison, it can be seen that adding an appropriate amount of the first additive and the second additive to the electrolyte at the same time can not only improve the high-temperature cycle performance and high-temperature storage performance, but also reduce the initial impedance of the battery, improve the low-temperature performance of the battery, and thus achieve the effect of taking into account the high and low temperature performance of the battery, especially when the addition amount of the first additive is 0.01% to 5%, it has a significant effect of reducing impedance and improving low-temperature discharge. When the addition amount of the first additive is 5% to 10%, more first additives may cause the battery interface film to be thicker, thereby weakening the effect of the additive composition in reducing the battery impedance, and at the same time, the high-temperature performance is gradually deteriorated, but it still has a certain effect of improving high temperature relative to the basic electrolyte.
[0120] Comparing Examples 1 to 10 in Table 1 with Comparative Examples 1 to 3 and Comparative Example 6, it can be seen that adding an appropriate amount of the second additive to the electrolyte containing the first additive can further improve the high temperature performance of the battery without increasing the initial DCR of the battery and without deteriorating the low temperature discharge performance of the battery. This is mainly because the cross-linked network structure formed by the first additive and the SO4 2- The combination of particles and boron atoms in the cross-linked network structure further improves the high-temperature stability of the interface film.
[0121] By comparing Example 9 with Comparative Examples 4 to 5 in Table 1 above, it can be seen that as the amount of the second additive added increases, excessive sulfate may block the ion transmission channel, aggravate the side reactions between the electrolyte and the electrode, thereby significantly increasing the initial DCR of the battery and deteriorating various battery performances.
[0122] Comparing Example 3 with Examples 11-12 in Table 1 above, it can be seen that continuing to add VC to the electrolyte containing the first additive and the second additive can further improve the battery cycle performance and high temperature storage performance; further adding PS to the electrolyte containing the first additive and the second additive can further improve the battery high temperature storage performance. Comparing Example 8 with Example 13, it can be seen that adding VC and LiDFP to the electrolyte containing the first additive and the second additive at the same time can further improve the overall performance of the battery.
[0123] Examples 14 to 15 and Comparative Examples 7 to 9 in Table 1 are the electrochemical performance test results of the additive composition applied to sodium ion batteries. Except that the initial DCR of the sodium ion battery is slightly greater than that of the corresponding lithium ion battery due to the material itself, the electrochemical performance test results of the above additive composition applied to lithium ion batteries and sodium ion batteries are basically consistent, that is, the combination of the first additive and the second additive in appropriate amounts can also improve the high and low temperature comprehensive performance of the sodium ion battery.
Claims
1. An electrolyte additive composition, characterized in that: The additive composition comprises: The first additive comprises at least a pyrosulfate boron trifluoride composite metal salt having a structure shown in the following formula (I-1): The second additive is selected from sulfates having structures shown in the following formulas (II) and / or (III): Wherein, M is Li or Na; The mass ratio of the second additive to the first additive is (0.001-0.1):
1.
2. The electrolyte additive composition according to claim 1, characterized in that: The mass ratio of the second additive to the first additive is (0.01-0.1):
1.
3. The electrolyte additive composition according to claim 1 or 2, characterized in that: The first additive further comprises at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6): In formula (I-2), (I-3), (I-4), (I-5), (I-6), M is Li or Na; The first additive contains at least 80 wt % of the pyrosulfate boron trifluoride composite metal salt having the structure represented by formula (I-1).
4. The electrolyte additive composition according to claim 3, characterized in that: The first additive contains 80 to 95 wt % of a pyrosulfate boron trifluoride complex metal salt having a structure represented by the formula (I-1), and the remainder is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).
5. A method for preparing a lithium ion battery electrolyte, characterized in that: The preparation method comprises: adding a main lithium salt to a non-aqueous solvent until the molar concentration of the main lithium salt is 0.1 to 4.0 mol / L, and then continuing to add the additive composition according to any one of claims 1 to 4 to obtain an electrolyte, wherein the first additive accounts for 0.01 to 15.0 wt% of the total mass of the electrolyte, and the second additive accounts for 0.001 to 0.5 wt% of the total mass of the electrolyte; The non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds; The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate, and lithium difluorobis(oxalatophosphate).
6. The method for preparing the electrolyte according to claim 5, characterized in that: The first additive accounts for 0.1-10.0 wt% of the total mass of the electrolyte, and the second additive accounts for 0.01-0.5 wt% of the total mass of the electrolyte.
7. The method for preparing the electrolyte according to claim 5, characterized in that: The C3-C6 carbonate or fluorocarbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate or ethyl propyl carbonate; the C3-C8 carboxylic acid ester or fluorocarboxylic acid ester compound is selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate and propyl propionate; the sulfone compound is selected from at least one of cyclopentane sulfoxide, dimethyl sulfoxide, dimethyl sulfone or diethyl sulfone; the ether compound is selected from triethylene glycol dimethyl ether and / or tetraethylene glycol dimethyl ether.
8. The method for preparing an electrolyte according to any one of claims 5 to 7, characterized in that: A basic additive is added to the electrolyte, wherein the basic additive is selected from at least one of fluoroethylene carbonate, vinylethylene carbonate, tris(trimethylsilyl)phosphate, 1,3-propylene sultone, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, lithium difluorobis(oxalate)phosphate or lithium difluorobis(oxalate)borate, and any one of the basic additives accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte.
9. A lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The lithium ion secondary battery is prepared by the following method: The positive electrode sheet, the separator and the negative electrode sheet are wound together into a core, sealed with an aluminum-plastic film and then baked, and then the electrolyte prepared by any preparation method described in claims 5-8 is injected therein, wherein the first additive and the second additive in the electrolyte are both lithium salts, and a lithium-ion secondary battery is obtained after standing, forming, volume separation and aging.
10. The lithium-ion secondary battery according to claim 9, characterized in that: The active material of the positive electrode plate is selected from nickel-cobalt-manganese ternary material, nickel-cobalt-aluminum ternary material, lithium cobalt oxide material or lithium iron phosphate material, and the active material of the negative electrode plate is selected from graphite, silicon carbon, silicon oxide, silicon, tin, metallic lithium or their composite materials.
11. A method for preparing a sodium ion battery electrolyte, characterized in that: The preparation method comprises: adding a main sodium salt to a non-aqueous solvent until the molar concentration of the main sodium salt is 0.1 to 4.0 mol / L, and then continuing to add the additive composition according to any one of claims 1 to 4 to obtain an electrolyte, wherein the first additive accounts for 0.01 to 15.0 wt% of the total mass of the electrolyte, and the second additive accounts for 0.001 to 0.5 wt% of the total mass of the electrolyte; The non-aqueous solvent is selected from at least one of C3-C6 carbonate or fluorinated carbonate compounds, C3-C8 carboxylic acid ester or fluorinated carboxylic acid ester compounds, sulfone compounds or ether compounds; The main sodium salt is selected from at least one of sodium hexafluorophosphate, sodium perchlorate, sodium difluorophosphate, sodium bis(oxalatoborate), sodium difluorooxalatoborate, sodium bis(trifluoromethylsulfonylimide) or sodium bis(fluorosulfonylimide).
12. The method for preparing the electrolyte according to claim 11, characterized in that: The first additive accounts for 0.1-10.0 wt% of the total mass of the electrolyte, and the second additive accounts for 0.01-0.5 wt% of the total mass of the electrolyte.
13. The method for preparing an electrolyte according to claim 11, characterized in that: The C3-C6 carbonate or fluorocarbonate compound is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate or ethyl propyl carbonate; the C3-C8 carboxylic acid ester or fluorocarboxylic acid ester compound is selected from at least one of γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate and propyl propionate; the sulfone compound is selected from at least one of cyclopentane sulfoxide, dimethyl sulfoxide, dimethyl sulfone or diethyl sulfone; the ether compound is selected from triethylene glycol dimethyl ether and / or tetraethylene glycol dimethyl ether.
14. The method for preparing an electrolyte according to any one of claims 11 to 13, characterized in that: A basic additive is added to the electrolyte, wherein the basic additive is selected from at least one of fluoroethylene carbonate, vinylethylene carbonate, tris(trimethylsilyl)phosphate, 1,3-propylene sultone, sodium difluorophosphate, sodium bis(fluorosulfonyl)imide, succinic anhydride, adiponitrile, cyclohexylbenzene, sodium bis(oxalyl)difluorophosphate or sodium difluorooxalatoborate, and any one of the basic additives accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte.
15. A sodium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The sodium ion secondary battery is prepared by the following method: The positive electrode sheet, the separator and the negative electrode sheet are wound together into a winding core, sealed with an aluminum-plastic film and then baked, and then the electrolyte prepared by any preparation method described in claims 11 to 14 is injected therein, wherein the first additive and the second additive in the electrolyte are both sodium salts, and a sodium ion secondary battery is obtained after standing, forming, volume separation and aging; The negative electrode of the sodium-ion battery is one or more of hard carbon, carbon black, amorphous carbon, graphite, SnS2, Na2Ti3O7, silicon-based materials, metal oxides, metal sulfides or metallic sodium; the positive electrode material is NaMn (1-x-y) Ni y M x O2 (0 ≤ x, y ≤ 1, M is Cu, Fe, Co), sodium manganate, sodium vanadium phosphate, sodium fluorovanadium phosphate, sodium iron phosphate, sodium manganese phosphate, Na x MnFe(CN)6 (0 < x ≤ 2), or one or more of them.
Citation Information
Patent Citations
High-energy-density battery electrolyte
CN118173885A
Application of pyrosulfate boron trifluoride composite lithium salt in electrolyte
CN118173890A
Lithium-ion battery electrolyte and lithium-ion battery containing same
CN111029653A
Electrolyte for lithium ion battery and lithium ion battery comprising electrolyte
CN112117491A
Non-aqueous electrolyte containing sulfur-containing lithium salt derivative additive and lithium ion battery
CN112349951A